Pemanfaatan platform Alef Education dalam pembelajaran Bahasa Arab di MTs Negeri 7 Blitar - Mutiara, Qholbi (Maliki Interdisciplinary Journal, 2023)
This article examines the use of the Alef Education platform as a learning media with an international curriculum that can be accessed by all madrasah students in Indonesia. The problem of decreased student interest and motivation in learning after the Covid-19 pandemic requires educators to package learning in a more interesting and easy to understand way. The use of appropiate media can encourage and motivate students in the learning process so that it will accelerate mastery of the material. The Alef Education platform is here as a new breakthrough for using internet-based applications that support active and fun learning for students. No research has been found that use the Alef Education platform as a media for learning Arabic in schools. Therefore, this research will examine the use of the Alef Education platform which has been accessible in Indonesia since 2021. The focus in this article is limited to the use of the Alef Education platform as a media for learning Arabic has succeeded in increasing student motivation and enthuasiasm so that it has an impact on increasing student learning outcomes. This increase has a positive influence on the quality of learning.